Overlapping Time-Lens Array - Avi Klein; Inbar Sibony; Sara Meir; Shir Shahal; Hamootal Duadi; Moti Fridman (IEEE Photonics Journal, 2019)
We suggest a time-lens array with a filling factor of 200% and increased resolution of 60% without decreasing the number of lenses in the array. This time-lens array is based on a series of orthogonally polarized time-lenses. We investigate the different nonlinear interactions and show that when the pump waves of two adjacent time-lenses have orthogonal states of polarization, it is possible to overlap by 50% without unwanted nonlinear interactions.